Designing a ridge filter based on a mouse foot skin reaction to spread out Bragg-peaks for carbon-ion radiotherapy. Issue 2 (May 2015) - Uzawa, Akiko; Ando, Koichi; Kase, Yuki; Hirayama, Ryoichi; Matsumoto, Yoshitaka; Matsufuji, Naruhiro; Koike, Sachiko; Kobashi, Gen
Abstract Background and purpose Carbon-ion radiotherapy uses spread-out Bragg peaks (SOBP) to produce uniform biological effects within a target volume. The relative biological effectiveness is determined by the in vitro cell kill after a single dose is employed to design the SOBP. A question remains as to whether biological effects for in vivo tissues after fractionated doses are also uniform within the SOBP. Material and methods Mouse foot skin was irradiated with fractionated doses of carbon ions at various linear energy transfer (LET) values. A new ridge filter was designed based on alpha and beta values for each LET to cause moderate skin reaction, and was studied concerning its uniformity. Results The reciprocal total doses of intermediate-LET carbon ions and of reference gamma rays linearly increased with an increase of a dose per fraction in Fe-plots. As the single total dose of higher LET run off linearity, data obtained from 2 to 6 fractions were used to design a new ridge filter. The physical dose distribution of the new ridge filter was almost identical to, and indistinguishable from, the ridge filter designed based on the in vitro cell kill. Conclusions The LET dependence of alpha is a principle of the biological factor to be used for designing spread-out Bragg peaks of carbon-ion radiotherapy.